Herpes Simplex Virus Hepatitis in an Immunocompetent Adult: A Fatal Outcome due to Liver Failure - Rachel A. Poley; Jaime F. Snowdon; Daniel W. Howes (Case Reports in Critical Care)
Objective. To present a case of a healthy 41-year-old female who developed fulminant hepatic failure leading to death. The cause of hepatic failure identified on postmortem exam was herpes simplex virus hepatitis. Design. Observation of a single patient. Setting. Intensive care unit of a tertiary care university teaching hospital in Canada. Patient. 41-year-old previously healthy female presenting with a nonspecific viral illness and systemic inflammatory response syndrome. Intervention. The patient was treated with intravenous fluids and broad-spectrum antibiotics. On the second day of admission, she was found to have elevated transaminases, and, over 48 hours, she progressed to fulminant liver failure with disseminated intravascular coagulopathy, refractory lactic acidosis, and shock. She progressed to respiratory failure requiring intubation and mechanical ventilation. She was started on N-acetylcysteine, a bicarbonate infusion, hemodialysis, and multiple vasopressors and inotropes. Measurements and Main Results. Despite treatment, the patient died roughly 70 hours after her initial presentation to hospital. Her postmortem liver biopsy revealed herpes simplex virus hepatitis as her cause of death. Conclusions. Herpes simplex virus must be considered in all patients presenting with liver failure of unknown cause. If suspected, prompt treatment with acyclovir should be initiated.